063 Enhancing the Uptake of Clinical Practice Guidelines: The Development of a Guideline Implementability Tool (Guide-It). (15th August 2013) - Kastner, M; Versloot, J; Hayden, L; Chatterjee, A; Bhattacharyya, O
Abstract : Background: Guidelines have the potential to facilitate implementation of evidence into practice but this has not been consistently achieved. We developed a guideline implementability tool (GUIDE-IT), which can assess the implementability of guideline recommendations. Objective: To determine if GUIDE-IT can improve the Language and Format of guideline recommendations. Methods: Using a mixed-methods approach to develop GUIDE-IT, we conducted 1) a Realist Review of guideline factors influencing uptake, and used its results to build a conceptual model of guideline implementability; 2) qualitative interviews with 20 family physicians to determine factors influencing guideline uptake and to obtain input on tool design; 3) created a prototype and conducted validity assessments with experts in guideline development and human factors. GUIDE-IT was then pilot tested with the Canadian Diabetes/Paediatric Associations (CDA, CPS) to determine its potential for assessing the implementability of guideline recommendations. Results: Pilot testing with CDA and CPS developers showed that factors across 4 sub-domains of Language (clarity, simplicity, specificity, and actionability) and 3 sub-domains of Format (presentation, components, and multiple versions) were applicable for modifying recommendations. GUIDE-IT was feasible to use by guideline developers to identify implementability problems and to improve recommendations. Discussion: GUIDE-IT is based on a robust evidentiary base with the potential to improve guidelines. Next steps include evaluating GUIDE-IT in a controlled trial to determine its impact on end-user clinical decision making. Implications for Guideline Developers/Users: GUIDE-IT has potential to be a practical tool for developers to improve the language and format of guideline recommendations.